Empirical Evaluation and Parametric Optimization of Stepped Versus Traditional Solar Stills using Taguchi’s Methodology - Krunalkumar B Patel; Tushar M Patel; Kadi Sarva Vishwa Vidyalay (Penerbit Universiti Kebangsaan Malaysia, 2025)
The escalating scarcity of potable water in remote and arid regions necessitates increased reliance on sustainable solutions, notably solar stills. The imperative need to achieve high productivity and peak hour e ffi ciency in these devices is critical to eff ectively addressing water shortages. This study explored modifi ed solar still designs aimed at improving the productivity and peak-hour effi ciency of the water desalination process. The experimental investigations involved various parameters, including water depth (10, 20, and 30 mm), mass fl ow rate (10, 15, and 20 kg/h), and glass thickness (4, 5, and 6 mm) for both traditional and stepped solar stills. The experimental layout followed an L18 orthogonal array. It was structured with 21×33 = 18 combinations, ensuring comprehensive coverage of the factors and levels involved, and the outputs were systematically examined using the Taguchi approach to identify the optimal parameter values. Stepped solar stills have emerged as superior, demonstrating higher peak-hour effi ciency and productivity than traditional solar stills. The most infl uential parameters, ranked by eff ectiveness, were the type of solar still, water depth, glass thickness, and mass fl ow rate. The optimal conditions for achieving maximum productivity (3881 ml) and peak hour e ffi ciency (22.03%) were identifi ed, including a stepped solar still, 10 mm water depth, 15 kg/h mass fl ow rate, and 4 mm glass thickness. The experimentally measured values were closely aligned with the predicted values, verifying the accuracy of the Taguchi model with minimal error (0.81% in productivity and 0.49% in peak hour effi ciency).